Asymptotic stability for a free boundary tumor model with a periodic supply of external nutrients. (June 2022) - Huang, Yaodan
Abstract: For tumor growth, the morphological instability provides a mechanism for invasion via tumor fingering and fragmentation. This work considers the asymptotic stability of a free boundary tumor model with a periodic supply of external nutrients. The model consists of two elliptic equations describing the concentration of nutrients and the distribution of the internal pressure in the tumor tissue, respectively. The effect of the parameter μ representing a measure of mitosis on the morphological stability are taken into account. It was recently established in Huang et al. (2019) that there exists a critical value μ ∗ such that the unique spherical periodic positive solution is linearly stable for 0 μ ∗ . In this paper, we further prove that the spherical periodic positive solution is asymptotically stable for 0 < μ < μ ∗ for the fully nonlinear problem.